Can Private Forecasters Beat the USDA? Analysis of Relative Accuracy of Crop Acreage and Production Forecasts. (2nd November 2020) - Isengildina-Massa, Olga; Karali, Berna; Irwin, Scott H.
Abstract: This study examines the accuracy of United States Department of Agriculture (USDA) crop Acreage and Production forecasts for corn, soybeans, and winter wheat relative to their private counterparts over 1970–2019. Our main findings suggest that USDA forecasts often had significantly smaller errors than their private counterparts. The accuracy of both USDA and private forecasts has improved over time, but the accuracy of USDA forecasts has improved more than that of private forecasts, maintaining the USDA's relative accuracy advantage. The accuracy advantage of Prospective Plantings and Acreage reports highlights the importance of survey-based approaches used for these forecasts.